Analysis Of Organizational Culture Aspects Post-Acquisition Of XY Mall (Case Study At Pt. X) - Neisya Esvandiary Iswari (Jurnal Scientia, 2024)
Acquisition is a term originating from English, which means taking over ownership of another party. In this case, PT. X acquires Mal XY from PT. Y. An organization or company certainly has its own organizational culture. Where organizational culture is a shared system of meaning embraced by its members that distinguishes it from other organizations. When an organization or company undergoes an acquisition, there will be adjustments to its organizational culture. This research is qualitative in nature with data collection techniques through literature review, field research, interview method approach, and the use of questionnaires in the form of the Organizational Culture Assessment Instrument (OCAI), with a case study at PT.X. The informants for this research are employees with positions ranging from Mal Manager, Supervisor, and Staff, all of whom are directly related to the acquisition of Mal XY. The results of this study indicate that PT. X has implemented a new organizational culture with a centralized structure. The current organizational culture tends towards the Market type, while the type of culture expected by employees tends towards the Clan type. However, the current and expected cultural types are not significantly different. Thus, it can be concluded that after the acquisition, there is no significant shift in the organizational culture at PT. X.